2001
DOI: 10.1128/iai.69.12.7493-7500.2001
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Antigen Expression in Live RecombinantSalmonella entericaSerovar Typhimurium Strongly Affects Colonization Capabilities and Specific CD4+-T-Cell Responses

Abstract: Regulated antigen expression can influence the immunogenicity of live recombinant Salmonella vaccines, but a rational optimization has remained difficult since important aspects of this effect are incompletely understood. Here, attenuated Salmonella enterica serovar Typhimurium SL3261 strains expressing the model antigen GFP_OVA were used to quantify in vivo antigen levels by flow cytometry and to simultaneously follow the crucial early steps of antigen-specific T-cell responses in mice that are transgenic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 51 publications
(50 reference statements)
4
52
0
Order By: Relevance
“…Alternatively, DO11.10 cells were stimulated in vitro with 1 M OVA peptide (amino acids 323-339) for 4 days before adoptive transfer. One day after transfer of unstimulated DO11.10 T cells or 4 days after transfer of prestimulated DO11.10 T cells, mice were orally infected with Ϸ5 ϫ 10 8 colony-forming units (cfu) of Salmonella, as described (18). At various time intervals after infection, mice were killed and Peyer's patches were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, DO11.10 cells were stimulated in vitro with 1 M OVA peptide (amino acids 323-339) for 4 days before adoptive transfer. One day after transfer of unstimulated DO11.10 T cells or 4 days after transfer of prestimulated DO11.10 T cells, mice were orally infected with Ϸ5 ϫ 10 8 colony-forming units (cfu) of Salmonella, as described (18). At various time intervals after infection, mice were killed and Peyer's patches were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Our western blot data demonstrated that the release of CtxB into the supernatant via its internal sec-dependent signal is, at minimum, very inefficient in Salmonella. Furthermore, although the tac-promoter has a comparable in vitro and in vivo activity, 47 the expression and the stability of CtxB in vivo might be lower than that in vitro. As a consequence, the extracellularly available level of native CtxB (in the form of pentamers) is very low and thus there is only negligible activity of CtxB as an immunostimulant.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant vector pTrcHis-F-I, carrying the hybrid gene of Met-Ala-(His) 6 OprF 190-342 -OprI 21-83 from P. aeruginosa was expressed by E. coli XL-1 Blue and purified as described previously (11,24). Subsequently, Met-Ala-(His) 6 OprF 190-342 -OprI 21-83 was adsorbed to aluminum hydroxide [Al(OH) 3 ] (Superfos; Vedbaeck, Denmark). The final concentration of the vaccine was 0.1 mg of OprF-I/ml and 0.3 mg of Al(OH) 3 /ml with 0.05 mg of thimerosal/ml (Caesar & Lorenz, Hilden, Germany) as preservative.…”
Section: Animalsmentioning
confidence: 99%
“…Escherichia coli Electro10 (Stratagene) was used for cloning. The oprFoprI fusion gene encoding Met-Ala-(His) 6 OprF 190-342 -OprI 21-83 from P. aeruginosa was cloned on pBR322-derived plasmids downstream of two constitutively active promoters (P yz [14] in pDB3 and P trc in pDB4) or the in vivo inducible Salmonella P pagC promoter (7,16) in plasmids pMW151, pMW209, and pMW210. These in vivo inducible constructs differed in the ribosomal binding site (33) upstream of oprF-oprI, resulting in differential in vivo OprF-OprI expression levels.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation